BENTUK PERTUNJUKAN DAN FUNGSI BUNDENGAN WONOSOBO - Bahtiar Arbi; Richard Junior Kapoyos (Tonika: Jurnal Penelitian dan Pengkajian Seni, 2019)
Bundengan is a musical instrument that is transformed from kowangan or tudhung. Kowangan is a kind of head covering made from bamboo slats, clumpring, and palm fibers that are used by duck herders to protect them from rain and sunlight. Bundengan is used as a dance accompaniment as in Lengger and Soreng. The purpose of this study is to analyze the form of performance and function of bundengan art. This study uses qualitative methods with data collection techniques interviews, observation, and study documents. Data validity techniques are based on credibility criteria, using data triangulation, while data analysis techniques are through data collection, presentation, reduction, and verification. This research approach uses an interdisciplinary qualitative approach, with intraesthetic studies on music forms and extraesthetics on music functions. The results of this study indicate that the form of the bundengan imitates the sound of gamelan (bendhe, kempul, gong, and kendang) applied to the pattern of the game to accompany the Lengger Topeng dance. While the function of bundengan music is as a dance accompaniment, emotional expression, aesthetic appreciation, entertainment, communication, related to social norms, cultural continuity, and community integration.